Improvement of DOPA-Melanin Production by Aspergillus nidulans Using Eco-Friendly and Inexpensive Substrates - Campanhol, Beatriz Silva [UNESP]; Ribeiro, Beatriz Dias [UNESP]; Casellato, Fernando [UNESP]; Medina, Kelly Johana Dussán [UNESP]; Sponchiado, Sandra Regina Pombeiro [UNESP] (MDPI, 2023)
Fungal pigments, including melanin, are recognized as promising materials for biomedical, environmental, and technological applications. In previous studies, we have demonstrated that the DOPA-melanin produced by the MEL1 mutant of Aspergillus nidulans exhibits antioxidant, anti-inflammatory, and antimicrobial activities without any cytotoxic or mutagenic effects, suggesting its potential use in pharmaceuticals. In order to increase the yield of this pigment and reduce the costs of its large-scale production, the present study aimed to evaluate agro-industrial by-products, sugarcane molasses, vinasse, and corn steep liquor as inexpensive substrates for fungal growth using experimental design methodology. According to the results obtained, the optimal composition of the culture medium was 0.81% (v/v) vinasse and 1.62% (w/v) glucose, which promoted a greater production of melanin (225.39 ± 4.52 mg g−1 of biomass), representing a 2.25-fold increase compared with the condition before optimization (100.32 mg.g−1 of biomass). Considering the amount of biomass obtained in the optimized condition, it was possible to obtain a total melanin production of 1 g L−1. Therefore, this formulation of a less complex and low-cost culture medium composition makes the large-scale process economically viable for future biotechnological applications of melanin produced by A. nidulans.
Keywords: Aspergillus nidulans; corn steep liquor; melanin; molasses; optimization; pigment; vinasse